Effect of Fructooligosaccharide Metabolism on Chicken Colonization by an Extra-Intestinal Pathogenic Escherichia coli Strain - Porcheron, Gaëlle; Chanteloup, Nathalie Katy; Trotereau, Angélina; Brée, Annie; Schouler, Catherine (PLOS ONE, 2012)
Extra-intestinal pathogenic Escherichia coli (ExPEC) strains cause many diseases in humans and animals. While remaining asymptomatic, they can colonize the intestine for subsequent extra-intestinal infection and dissemination in the environment. We have previously identified the fos locus, a gene cluster within a pathogenicity island of the avian ExPEC strain BEN2908, involved in the metabolism of short-chain fructooligosaccharides (scFOS). It is assumed that these sugars are metabolized by the probiotic bacteria of the microbiota present in the intestine, leading to a decrease in the pathogenic bacterial population. However, we have previously shown that scFOS metabolism helps BEN2908 to colonize the intestine, its reservoir. As the fos locus is located on a pathogenicity island, one aim of this study was to investigate a possible role of this locus in the virulence of the strain for chicken. We thus analysed fos gene expression in extracts of target organs of avian colibacillosis and performed a virulence assay in chickens. Moreover, in order to understand the involvement of the fos locus in intestinal colonization, we monitored the expression of fos genes and their implication in the growth ability of the strain in intestinal extracts of chicken. We also performed intestinal colonization assays in axenic and Specific Pathogen-Free (SPF) chickens. We demonstrated that the fos locus is not involved in the virulence of BEN2908 for chickens and is strongly involved in axenic chicken cecal colonization both in vitro and in vivo. However, even if the presence of a microbiota does not inhibit the growth advantage of BEN2908 in ceca in vitro, overall, growth of the strain is not favoured in the ceca of SPF chickens. These findings indicate that scFOS metabolism by an ExPEC strain can contribute to its fitness in ceca but this benefit is fully dependent on the bacteria present in the microbiota.